KEMAMPUAN PEMECAHAN MASALAH SARJANA PENDIDIKAN FISIKA PADA TOPIK DINAMIKA ROTASI (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2020)
The steps of physics problems solving consist of making a useful description, determining physics approach, applying specific application of physics, performing mathematical procedures, and evaluating logical progression of the problem solving process. Physics is closely related to everyday problems, including rotational dynamics problems. Bachelor of physics education must have conceptual understanding to create learnings that improve students' problem solving skills. Therefore, this study aimed to measure the problem-solving skills of bachelors of physics education involving 10 bachelors of physics education who were working as science teachers. This study was a descriptive study with data collection using essay question. The results showed that there were difficulties in solving problems consisted of difficulties in drawing vectors and operating them and difficulties in understanding the rotational dynamics concepts. These results indicated the importance of learning and improving conceptual understanding as the main asset in teaching the material for bachelors of physics education.